Analisis Pengaruh Kerapatan Vegetasi Ruang Terbuka Hijau (RTH) Terhadap Intensitas Cahaya Matahari dan Suhu Udara (Studi Kasus: Kota Jambi) - Anggrika Riyanti; G M Saragih; Nur Fauziah Zahratu Qolbi (Universitas Batanghari Jambi, 2021)
Increasing urban population growth has causing unbalanced development which has a negative impact on green open space. Jambi City has 14.92 ha of green open space. When compared with the area of Jambi City, it is found that green open space is only 8.76%. One of the impacts of reducing green open space is the increase in air temperature in Jambi City every year. This study aims to analyze the effect of vegetation density on green open space on light intensity and air temperature in Jambi City. The research case studies were in Kota Baru, Telanaipura, and Pasar Jambi Districts which selected based on zoning of green open space covered with a density level of rarely, medium and dense (Regulation of the Director of Planning of the Ministry of Forestry Number 3/2014). The effect of vegetation density on light intensity and air temperature was statistically analyzed using Pearson correlation. The results showed that vegetation density in green open spaces had a significant effect on light intensity with a strong correlation value of 0.704. Vegetation density also had a significant effect on air temperature with a moderate correlation value of 0.575.